Selected issues of trade secrets of business entities in contractual relations in Ukraine - Яфонкін, Анатолій Олексійович; Климко, Вікторія Сергіївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2016)
The article highlights some of the problems of protection of trade secrets, clarified Roots and leakage of commercial information to the entities proposed ways to protect them. Particular attention is paid to deliver commercial secrets contained in the agreements (contracts) concluded between business entities, individual problems that impede the efficient protection of trade secrets to unscrupulous competitors. At the present stage of economic development issues, information provision business is very relevant. To maintain a safe and economically reasonable economic activity in Ukraine should create the right conditions, including in information sphere. The article deals with some problems of protection of trade secrets give reasons and creep age commercial information on the subjects of management, ways of their protection. Particular attention is paid to the types of trade secrets contained in the agreements (contracts) concluded between economic entities, as well as specific issues that make it difficult to organize an effective trade secrets protection from unfair competition. Emphasized that the growing array of information, improvement of technical means of its storage, processing and transmission requires the introduction of new methods, techniques and ways of its protection based on existing legislation. The author offered his views on solving the above problems.